TRH Analog, Taltirelin Protects Dopaminergic Neurons From Neurotoxicity of MPTP and Rotenone - Zheng, Cong; Chen, Guiqin; Tan, Yang; Zeng, Weiqi; Peng, Qiwei; Wang, Ji; Cheng, Chi; Yang, Xiaoman; Nie, Shuke; Xu, Yan; Zhang, Zhentao; Papa, Stella M.; et al. (Frontiers in Cellular Neuroscience, 2018)
Dopaminergic neurons loss is one of the main pathological characters of Parkinson’s disease (PD), while no suitable neuroprotective agents have been in clinical use. Thyrotropin-releasing hormone (TRH) and its analogs protect neurons from ischemia and various cytotoxins, but whether the effect also applies in PD models remain unclear. Here we showed that Taltirelin, a long-acting TRH analog, exhibited the neuroprotective effect in both cellular and animals models of PD. The in vitro study demonstrated that Taltirelin (5 μM) reduced the generation of reactive oxygen species (ROS) induced by MPP+ or rotenone, alleviated apoptosis and rescued the viability of SH-SY5Y cells and rat primary midbrain neurons. Interestingly, SH-SY5Y cells treated with Taltirelin also displayed lower level of p-tau (S396) and AEP cleavage products, tau N368 and α-synuclein N103 fragments, accompanied by a lower intracellular monoamine oxidase-B (MAO-B) activity. In the subacute MPTP-induced and chronic rotenone-induced PD mice models, we found Taltirelin (1 mg/kg) significantly improved the locomotor function and preserved dopaminergic neurons in the substantia nigra (SN). In accordance with the in vitro study, Taltirelin down-regulated the levels of p-tau (S396), p-α-synuclein (S129) tau N368 and α-synuclein N103 fragments in SN and striatum. Together, this study demonstrates that Taltirelin may exert neuroprotective effect via inhibiting MAO-B and reducing the oxidative stress and apoptosis, preventing AEP activation and its subsequent pathological cleavage of tau and α-synuclein, thus provides evidence for Taltirelin in protective treatment of PD.